2018
DOI: 10.1109/lpt.2018.2879365
|View full text |Cite
|
Sign up to set email alerts
|

Time-Division Parallel FDTD Algorithm

Abstract: We propose a novel and efficient algorithm to parallelize the finite-difference time-domain method, where the observation period is divided into an arbitrary number of subsections, whose computation is distributed to corresponding computer nodes. The proposed algorithm roughly reduces the computational time to an nth fraction of the conventional algorithm, where n is the number of nodes for parallel computing, thus verifying its efficiency improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…Table II compares the computational times of parallel IFFT (inverse fast Fourier transform) [23] and FILT for varying numbers of nodes. The frequency-domain or CFD data were transformed into time-domain, and the data length was 2 15 . It can be observed that for a single or few nodes, IFFT is faster than FILT.…”
Section: Computational Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table II compares the computational times of parallel IFFT (inverse fast Fourier transform) [23] and FILT for varying numbers of nodes. The frequency-domain or CFD data were transformed into time-domain, and the data length was 2 15 . It can be observed that for a single or few nodes, IFFT is faster than FILT.…”
Section: Computational Resultsmentioning
confidence: 99%
“…We recently developed a novel technique for conducting both time-and frequency-domain analyses; specifically, we combined FILT with the finite-difference complexfrequency-domain (FDCFD) method [12] for the near-field analysis of plasmonic objects. We also developed a time-division algorithm for the finite-difference time-domain (FDTD) technique [15]. This algorithm combines the FDTD [16], FDCFD, and FILT methods.…”
Section: Introductionmentioning
confidence: 99%
“…By truncating the infinite series, the final expression can be obtained as, where k is the truncation number. Here, the accuracy of f ec can be controlled by an approximation parameter α [14], [15]. The instantaneous field distribution at an observation time t can be accurately and efficiently solved using the summation in Eq.…”
Section: Formulation a Fast Inverse Laplace Transformmentioning
confidence: 99%
“…Our precise time domain electromagnetic responses can be obtained using the following procedure: rigorous solutions or highly accurate numerical results of electromagnetic waves are computed in the complex frequency domain. The waves in the complex frequency domain are numerically transformed into time domain using fast inversion of Laplace transform (FILT) [14], [15]. The instantaneous value is easily and efficiently obtained.…”
Section: Introductionmentioning
confidence: 99%
“…In the next step, the information used in the computations of electromagnetic fields is transformed. In the FDTD algorithm operations performed on the GPU, so there is no data transfer process because all calculations are performed on the GPU [16][17][18][19].…”
Section: Realization Of the Fdtd Model On Gpumentioning
confidence: 99%